Industrial relations and labour market policies in Ireland, Portugal and Slovenia - Hočevar, Marko (Teorija in praksa, 2024)
The article explores three countries with different industrial relations institutions: Ireland, Portugal and Slovenia. It focuses on the trajectories these countries have taken since the mid/late 1980s and compares the developments in their respective industrial relations systems, the role of their tripartite social dialogue bodies, and labour market policies. The article reveals similarities among the countries in their pursuit of industrial relations liberalisation and greater labour market flexibility. However, it also shows an opposite movement in these countries since 2015 and provides an explanation for these developments. The article thereby contributes to the different discussions in the field of comparative political economy dealing with the varieties of capitalism, institutional convergence and divergence, and the neoliberalisation of different industrial relations systems.
Keywords: EU; industrial relations; industrijski odnosi; labour markets; Odnosi med delodajalci in delojemalci; politics; politika; različice kapitalizma; Trg dela; trg delovne sile; varieties of capitalism